The role of big five personality dimensions in Indonesian teachers’ subjective career success - Tri Muji Ingarianti; Fendy Suhariadi; Fajrianthi Fajrianthi; Dini Lutfia; Devina Andriany (International Journal of Evaluation and Research in Education (IJERE), 2023)
Teachers hold strategic roles in the education system, and their career success is important to make sure they are strongly motivated at work. The big five personality is one of the personality approaches to form one’s subjective career success. This study aimed to identify the role of each dimension of the big five personality in affecting teachers’ subjective career success in Indonesia. To this end, the subjective career success inventory and personality item pool-big five factor makers were employed. This quantitative correlational study involved 320 teachers as respondents. The data were analyzed using multiple linear regression test. The result showed that dimensions of extraversion (p<0.000), agreeableness (p<0.000), and conscientiousness (p<0.001) influence Indonesian teachers’ subjective career success. These three dimensions show that teachers in Indonesia tend to have personalities related to other people’s acceptance or awareness of their social environment to attain subjective career success. Such personalities help them consider their personality and its aspects in evaluating their career.